Constraints Faced by Tomato Growers at Production and Marketing Level in Haryana - Anamika,; Ghalawat, Suman; Goyal, Megha; Malik, Joginder Singh; Bishnoi, Dalip Kumar (Indian Journal of Extension Education, 2023)
The tomato is the most consumed vegetable in raw or processed form in every house and its demand is throughout the year. The present study was carried out in the Kurukshetra, Karnal, and Yamunanagar Districts of Haryana in 2022-23. The data was collected from a sample of 210 farmers with the help of a well-structured interview schedule with the objective to study the constraints faced at the production and marketing levels. The analysis of data was done with the Garrett ranking technique. The study concluded that the major problem at the production level was climate vagaries (79.01), high labor cost (74.60), high incidence of insect, pest, and disease (70.52), high cost of tomato seed (62.75) and lack of skilled labor during peak time (59.79). At the marketing level, frequent price fluctuation (82.90), lack of cold storage and warehouse facilities (72.38), high transportation cost (68.83), and quality deterioration during transportation (61.07) were found to be major constraints. Extension programs focused on creating awareness among farmers on prevailing schemes, subsidies and hi-tech farming methods such as controlled climate production can be helpful in overcoming the constraints.
Keywords: Tomato cultivation; Production constraints; Marketing constraints; Farmers; Haryana